Moving to Catch Up : Migration of Ex-combatants in Uganda - Baxter, David; Burrall, Alexandra (World Bank, Washington, DC, 2017)
The purpose of this study was to provide a better understanding for policy makers and service providers of mobility and migration among ex-combatants and the effectiveness of Disarmament, Demobilization and Reintegration (DDR) programming in Uganda. The study followed a scoping study on migration in Uganda conducted in March 2011 by the Transitional Demobilization and Reintegration Program (TDRP) of the World Bank. This study had the following specific objectives: 1) to analyze push/pull migration factors of ex-combatants in Uganda, with a specific focus on social as well as economic factors both within communities of origin and at new communities of re-settlement; 2) to explore any impact of DDR programming on migration of ex-combatants in Uganda; 3) to increase the understanding of the impact of migration by ex-combatants on the effectiveness of past and current DDR programming, specifically on reintegration efforts; and 4) to generate recommendations on how to improve DDR programming, taking into account findings from other related studies.